Analysis of Digital Marketing Strategy at Almeera Atelier - Nur, Dini Hajah; Yusuf, Ismail; Koeswandi, Tika (A Social Science and Entrepreneurship Journal, 2022)
This research was conducted in order to help optimize the digital marketing strategy implemented to be more efficient and on target. This research uses a qualitative descriptive approach with STP (Segmenting, Targeting, Positioning), Marketing Mix 7P, and SWOT analysis methods. Describes the data obtained from the research results then the conclusion is drawn to determine the digital marketing strategy that is in Almeera Atelier. Based on the results of the analysis, the researchers concluded that the digital marketing strategy that Almeera Atelier can use is to optimize social media accounts